2005
DOI: 10.1086/431508
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Burden of Rotavirus Diarrhea in Thailand: Results of Sentinel Surveillance

Abstract: Diarrhea remains an important cause of morbidity and mortality among children in Thailand, with >1 million cases reported in 2002. In anticipation of the development of vaccines against rotavirus, we evaluated the disease burden associated with rotavirus infection in Thai children and evaluated the rotavirus serotypes now circulating in Thailand. Diarrhea surveillance was conducted at 6 Thai hospitals in different geographic areas. Community-based surveillance was conducted in Huaykrajao District, Kanchanaburi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 14 publications
4
50
4
1
Order By: Relevance
“…These findings support the need for continuous surveillance of the disease in various locations. Our study found a high incidence of rotavirus infection in Yogyakarta, Indonesia, which is comparable to the findings of similar studies in surrounding countries, such as Malaysia (38%) (21), Thailand (43%) (22), Cambodia (56%) (23) and Myanmar (57%) (24). Our study provides evidence that rotavirus infection gives a substantial burden to the one sample was identified as G3.…”
Section: From February To August 2009 104supporting
confidence: 88%
“…These findings support the need for continuous surveillance of the disease in various locations. Our study found a high incidence of rotavirus infection in Yogyakarta, Indonesia, which is comparable to the findings of similar studies in surrounding countries, such as Malaysia (38%) (21), Thailand (43%) (22), Cambodia (56%) (23) and Myanmar (57%) (24). Our study provides evidence that rotavirus infection gives a substantial burden to the one sample was identified as G3.…”
Section: From February To August 2009 104supporting
confidence: 88%
“…The detection of rotavirus in 31.2% of children hospitalized with acute gastroenteritis is similar to results from other countries in the region such as Thailand 17 and Malaysia 18 where rotavirus was associated with 39% and 38% of diarrheal hospitalizations, respectively. A study in Fiji found a similar disease burden (39%) and age distribution of rotavirus infections; however, G3P [8] was the predominant genotype, constituting 85% of the rotavirus strains detected in that study.…”
supporting
confidence: 81%
“…The studies of rotavirus infection carried out in Thailand revealed that rotaviruses are the leading etiologic pathogens that causes diarrhea in children, and are responsible for about 27-58% of diarrheal diseases in hospitalized cases [Maneekarn and Ushijima, 2000;Jiraphongsa et al, 2005;Khamrin et al, 2006b]. Epidemiological surveillance of group A rotavirus infection conducted in Chiang Mai, Thailand, during the period of 2000-2004 [Khamrin et al, 2006b[Khamrin et al, , 2007c During these extensive epidemiological studies, rotavirus strains with unusual G-P combinations were occasionally detected in children hospitalized with acute gastroenteritis; for example, an unusual strain of human rotavirus G3P[3] (CMH222) bearing simian-like VP7 and caprine-like VP4 genes was isolated from a 2-year-old child patient in 2001 [Khamrin et al, 2006a].…”
Section: Discussionmentioning
confidence: 99%